PENGARUH PELATIHAN VERTICAL RESCUE TERHADAP PENINGKATAN KETERAMPILAN SEARCH AND RESCUE DALAM MENOLONG KORBAN BENCANA - Yuniar Wardani; Purwadi (MEDIA ILMU KESEHATAN, 2017)
Background: Asian countries face disasters annually. Increasing vulnerability of people in Asia, especially related to demography, social and economic change technology fastly. Any person affected by disasters, with the expected first priority is to get help meeting basic needs and either given by the general public or trained personnel such as Search and Rescue. SAR must have a variety of skills such as skills in giving Basic Life Support also Vertical Rescue. Objective: The purpose of this study was to determine the effect of VR training to increase skills and Rescue. Methods: The type and design of the study were selected by the researchers was an experiment quasi with cross sectional approach. Variable measurement skills performed before and after the implementation of training and analyzed using Paired t test. Results: No effect of VR training to increase knowledge (p = 0.09), there was the effect of VR training on the improvement of the attitude (p = 0.00) and there was increased influence of VR on skill improvement (p = 0.00). Conclusion: There was the effect of VR training to increase attitude and skills of rescue in helping victims of the disaster. Keywords: Training, VR, skills, SAR